THE EXPRESSION OF LOVE IN THE POEM NÄHE DES GELIEBTEN BY JOHANN WOLFGANG VON GOETHE (A STRUCTURAL-SEMIOTIC STUDY) - Patricia Tampanguma; Sjuul J. Lendo; Prilimercy E. Kojongian (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research aims to describe and analyze the inner structure, physical structure as well as the meaning of the expression of love contained in the poem Nähe Des Geliebten by Johann Wolfgang Von Goethe. The method used in this research is a qualitative descriptive method with library research as a data collection technique and a structural-semiotic approach as a data analysis technique. In the structural approach there are the essence of poetry and poetic methods, while in semiotics there are heuristic readings, hermeneutic readings, and three aspects of signs according to Pierce namely Icons, Indexes and Symbols. The results of this study conclude that the interesting thing that can be expressed from the poem "Nähe Des Geliebten" is that this poem tells about the extraordinary feelings of love from a woman for her boyfriend. Even though they can't meet and are separated by distance, it doesn't make a woman stop thinking about her lover. The woman faithfully awaits the arrival of her lover every time. And there are various expressions of love that researchers have found in the study of Nähe Des Geliebten's poetry through three aspects of iconic signs, indexes, and symbols according to Pierce, namely expressions of falling in love, restlessness, longing and desire.